Through-the-coating femtosecond laser inscription of very short fiber Bragg gratings for acoustic and high temperature sensing applications - Hnatovsky, Cyril; Grobnic, Dan; Mihailov, Stephen J (Optics express, 2017)
Very short Type I and Type II Bragg gratings, on the order of 100 µm in length, are written through the protective polyimide coating of high NA and standard single mode silica optical fibers with infrared femtosecond pulses and a phase mask. By exploiting the transverse walk-off of apertured diffracted beams produced by the phase mask and a slit placed proximate the mask, complex grating structures are fabricated and characterized. These gratings are suitable for structural health monitoring based on acoustic measurements or localized high-temperature measurements.